The Influence of Job Embeddedness and Career Development on Employee Performance with Organizational Commitment as Variable Intervening: Study on Employees at Garment Factory in Semarang - Ariadi, Gede; Noegrahantie, Sofi Shellyana (Journal of Economics, Assets, and Evaluation, 2025)
This research examines the influence of job embeddedness and career development on employee performance with the mediating role of organizational commitment. This research uses a quantitative, explanatory approach with 100 respondents, employees of the Garment Factory in Semarang in the cutting department. The analysis in this research uses PLS-SEM (Partial Least Squares - Structural Equation Method). Based on the results of this research, it shows that: (i) job embeddedness influences employee performance; (ii) career development has no effect on employee performance; (iii) job embeddedness influences organizational commitment; (iv) career development influences organizational commitment; (v) organizational commitment influences employee performance; (vi) organizational commitment mediates the influence of job embeddedness on employee performance; Organizational commitment mediates the influence of career development on employee performance.